(untitled) (Journal of the College of Basic Education, 2026)
This research aimed to analyze the impact of climatic variation on potato crop yield in Wasit Governorate, and to determine the extent of this variation in climatic elements and its effect on the productivity of this strategic crop. The research methodology employed both descriptive and analytical approaches to determine the average percentage change in crop yield over the period from 1993 to 2022. The general trend rate and the percentage change rate were used as statistics. Four climatic monitoring stations were selected: Baghdad, Hilla, Al-Hay, and Diwaniyh. The research concluded that there is a variation in the studied climatic elements and phenomena, and that this variation influences potato crop yield in Wasit Governorate. Specifically. the percentage change in actual solar irradiance and the maximum and minimum temperatures at the Al- Hay base station showed a downward trend of (– 1.8 % , -1.02 %, and -3.99 %) respectively.